Successful mepolizumab treatment for DRESS-induced refractory eosinophilic myocarditis and concurrent thyroiditis. Issue 7 (15th July 2021) - Truong, Kelvin; Kelly, Shane; Bayly, Angela; Smith, Annika
Abstract : Drug reaction with eosinophilia and systemic symptoms (DRESS) is a potentially life-threatening adverse drug reaction with a mortality rate of 10%. Interstitial nephritis, pneumonitis, myocarditis, meningitis, thyroiditis and pancreatitis are major causes of morbidity and mortality in this syndrome. Cessation of offending medication is paramount. There is paucity in high quality prospective studies guiding the treatment of DRESS, and there are no published therapeutic clinical trials in the treatment of corticosteroid refractory hypersensitivity myocarditis. The authors present a unique case of ciprofloxacin-induced DRESS with concurrent thyroiditis and refractory eosinophilic myocarditis that required mepolizumab and multiple immunosuppressants for successful treatment.